Comprehensive Review of Laboratory Automation, Quality Control, And Workforce Adaptation - Alyami, Abdulaziz Abdullah; Alaqil, Naif Mana; Alsulayyim, Ali Salem Mana; Al yami, Ramzi Mubarak Khayri; Salem, Fatimah Jaber Mohd; Al hatailah, Abdullah Maadi Hussain; Al zandan, Salem Abdullah; Al Mushref, Sultan Akram Nasser; AL Musharraf, Saleh Akram Nasser; Balharith, Ali Saleh (Journal of Ecohumanism, 2024)
There is a very close relationship that exists between the increased use of automation technology and the quality of diagnosis as well as the efficiency of the laboratory. Therefore, this review intends to describe the current position of automation for laboratory facilities and sample analysis and investigate its impact on quality control (QC), efficiency, and workforce flexibility. Automated technologies have been integrated into all functional ranges, beginning from sample management to result determination, increasing the sample & result turnaround time and accuracy. Nevertheless, automation and incorporation of technologies in laboratories have their own issues, such as quality assurance, human resource changes, and flow process challenges. This review summarizes the current literature with advances in laboratory automation, quality control, and workforce management, together with implications for the future of laboratories in clinical and research settings.